The Trans Panic Defense: Masculinity, Heteronormativity, and the Murder of Transgender Women - Lee, Cynthia (2014)
When a heterosexual man is charged with murdering a transgender woman with whom he has been sexually intimate, one defense strategy is to assert what has been called the trans panic defense. The defendant claiming this defense will say that the discovery that the victim was biologically male provoked him into a heat of passion causing him to lose self-control. If the jury finds that the defendant was actually and reasonably provoked, it can acquit him of murder and find him guilty of the lesser offense of voluntary manslaughter. The trans panic defense strategy is troubling because it appeals to stereotypes about transgender individuals as sexually deviant and abnormal. In this article, we examine the cultural structures of masculinity that may lead a man to kill a transgender woman with whom he has been sexually intimate. Building on Professor Angela Harris’ important work on male-on-male violence, we argue that violence by men against transgender women is a variant of gender violence that has not received the attention it deserves. We examine how masculinities theories can unmask the motivations behind the trans panic defense and discuss ways in which structures of masculinity can encourage juries to find that the defendant who claims trans panic was reasonably provoked. Most critics of the trans panic defense strategy have argued that defendants should be banned from making trans panic arguments. Instead of advocating a ban on this defense strategy, we offer a tool kit of strategies for prosecutors to combat claims of trans panic. One of several suggestions we offer is a rephrasing of terminology, replacing the phrase “trans panic” with “trans rage.” We also argue that the current understanding of reasonableness in provocation doctrine¬¬—reasonableness as that which is typical—is misguided. We suggest reasonableness is better understood as a normative limitation on the provocation defense